2020
DOI: 10.1038/s41598-020-79159-4
|View full text |Cite
|
Sign up to set email alerts
|

Molar occlusion and jaw roll in early crown mammals

Abstract: Triconodontidae are considered the first carnivorous crown mammals. A virtual reconstruction of the masticatory cycle in the Late Jurassic Priacodon showed that triconodontid dental function is characterized by precise cutting on elongated crests. The combination of traits linked to both carnivorous diets (e.g. fore-aft cutting edges) and insectivorous diets (transverse crests and lobes) suggests a varied faunivorous diet appropriate to the small body size of most triconodontids. Total length of molar shear de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
(58 reference statements)
0
12
0
Order By: Relevance
“…Mammalian molars evolved from simple, conical precursor forms (haplodontic) with one cusp (protocone) and one root, more or less rotationally or bilaterally symmetric. The triconodontic upper molar scheme shows two roots and three main cusps (paracone, protocone and metacone, with smaller additional cusps), in upper molars arranged more or less in a single row [56,57]. A triconodontic tooth scheme, therefore, shows bilateral symmetry to a frontal plane and to a sagittal plane.…”
Section: Symmetry Of Teeth and Dental Archesmentioning
confidence: 99%
“…Mammalian molars evolved from simple, conical precursor forms (haplodontic) with one cusp (protocone) and one root, more or less rotationally or bilaterally symmetric. The triconodontic upper molar scheme shows two roots and three main cusps (paracone, protocone and metacone, with smaller additional cusps), in upper molars arranged more or less in a single row [56,57]. A triconodontic tooth scheme, therefore, shows bilateral symmetry to a frontal plane and to a sagittal plane.…”
Section: Symmetry Of Teeth and Dental Archesmentioning
confidence: 99%
“…Our predicted body mass range of 57.73-128.97 g based on molar length, 16.38-51.04 g based on molar width, 37.50 g based on humeral length, and 30.60 and 26.03 g based on the diameter of the humerus. Notably, the predictions derived from the humerus midshaft diameter are only about 75% of the magnitude of predictions by Jäger et al (2020) based on humeral circumference (40.9-45.9 g). This means that the partial discrepancy between predictions based on craniodental and postcranial predictors in P. fruitaensis is greater in our study than what they reported, but consistent with the rest of the taxa within Triconodontidae in this study.…”
Section: Cranial-postcranial Disparity In Triconodontid Body Mass Pre...mentioning
confidence: 75%
“…For example, the estimated basal metabolic rate of triconodontids is only half of that calculated using previous body mass predictions (0.5 W for a 100 g mammal and 0.23 W for a 30 g mammal; Kolokotrones et al 2010). The smaller predicted body mass of triconodontids also suggest that while some may have incorporated both vertebrate and invertebrate prey into their diets (Jäger et al 2020), most probably subsisted primarily on invertebrates. The nuance of these patterns opens a wide range of potential future research, including exactly how such constraints relate to the proximate genetic and developmental drivers of these dynamics.…”
Section: Re-evaluation Of Eutriconodonta Body Massmentioning
confidence: 77%
See 1 more Smart Citation
“…These differences include a single replacement, rather than continual loss and replacement of teeth (diphydonty rather than polyphydonty), heterodonty (varied tooth shapes in different parts of the jaw) rather than homodonty (uniform tooth shapes throughout the jaw), and most importantly for the evolution of the TMJ, occlusion of the upper and lower dentition. Occlusion is facilitated by complimentary cusp patterns in the upper and lower dentition for shearing and crushing of food items (Crompton, 1981 ; Grossnickle et al, 2021 ; Jäger et al, 2020 ). The changes in the dentition would have put more strain on the primary jaw joint, leading to the added involvement of additional bones to buttress these effects and support the jaw during movement (Crompton & Hylander, 1986 ).…”
Section: Architecture Of the Tmjmentioning
confidence: 99%